Preparation, escalation, de‐escalation, and normal activities. Issue 5 (16th September 2020) - Sadeghipour, Parham; Mohebbi, Bahram; Mousavizadeh, Mostafa; Hosseini, Saeid; Maleki, Majid
Abstract: Iran is one of the earliest countries involved with coronavirus disease 2019 (COVID‐19) pandemic. In the present short report, we have presented our experiences as a cardiovascular tertiary center during the COVID‐19 outbreak. At the beginning, we have pursued our activities in four field of administrative, preventative, therapeutic, and research. Then by gaining new experiences, we have tailored our strategies. Finally, we have described our challenges and future strategies on returning to normal activities.